Why a painting is like a pizza : a guide to understanding and enjoying modern art - Heller, Nancy (Princeton University Press, 2002)
Comparing modern art not only to pizzas but also to traditional and childrenUs art, a professor of art history shows readers how people can refine analytical tools they already possess to understand and enjoy even the most unfamiliar paintings and sculptures. 49 color illustrations. 40 halftones.